Pengembangan Aplikasi Kesehatan Peduli Diri Lindungi Sekitar (PDLS) untuk Pengabdian Masyarakat di Era Pandemi - Handoko, Erfan; Anastasya, Dhea Tri; Mustikasari, Diyan; Windiastuti, Tia; Utami, Yuliyanti Dwi; Pratama, Mutiara; Widowati, Retno (Mitra Teras: Jurnal Terapan Pengabdian Masyarakat, 2022)
Abstract In 2020, the development of the transmission of Covid-19 was quite significant because it has spread worldwide, and all countries are feeling its effects, including Indonesia. The government has announced an increase in Covid-19 cases, thus designating Covid-19 as a national disaster. One of the efforts to reduce the transmission of Covid-19 is the government’s implements Social Distancing. The public can determine whether they have contracted this disease by undergoing a Rapid Test. If they test positive, they will be retested using the Polymerase Chain Reaction (PCR) test method, which is far more accurate. Therefore, many government and non-government institutions provide online Covid-19 self-checkups. Providing education about Covid-19 is also important; one way is through an integrated application. The integrated application in question can provide routine notifications and information through infographics, online Covid-19 self-checkups, and self-checklists for entering and leaving the house to prevent Covid-19. Abstrak Pada tahun 2020, perkembangan penularan Covid-19 cukup signifikan karena penyebarannya sudah mendunia dan seluruh negara merasakan dampaknya termasuk Indonesia. Pemerintah telah mengumumkan peningkatan jumlah kasus Covid-19, sehingga menetapkan Covid-19 sebagai bencana nasional. Salah satu upaya untuk mengurangi penularan Covid-19 pemerintah menerapkan Social Distancing. Adapun masyarakat dapat mengetahui dirinya tertular penyakit ini atau tidak dengan menjalani Rapid Test, apabila dinyatakan positif akan diuji ulang dengan metode tes Polymerase Chain Reaction (PCR) yang jauh lebih akurat. Oleh sebab itu banyak Lembaga baik pemerintah maupun non pemerintah yang menyediakan self-checkup Covid-19 secara online. Pemberian edukasi mengenai Covid-19 juga penting untuk dilakukan, salah satu caranya dapat melalui aplikasi yang terintegrasi. Aplikasi terintegrasi yang dimaksud dapat memberikan notifikasi secara rutin, memberikan informasi melalui infografik, self-checkup Covid-19 secara online, dan ceklis diri prosedur keluar masuk rumah sebagai upaya pencegahan Covid-19.